The anti-proliferative activity of BTG/TOB proteins is mediated via the Caf1a (CNOT7)/Caf1b (CNOT8) deadenylase enzymes - Doidge, Rachel L. (2013)
The human BTG/TOB protein family comprises six members (BTG1, BTG2/PC3/Tis21, BTG3/Ana, BTG4/PC3B, TOB1/Tob, and TOB2) that display anti-proliferative activity in a number of cell types. They are characterised by a conserved N-terminal BTG domain that mediates interactions with the Caf1a (CNOT7) and Caf1b (CNOT8) deadenylases. It was unclear whether the anti-proliferative activity of the BTG/TOB proteins was mediated through interactions with Caf1a (CNOT7) and Caf1b (CNOT8). To address this we further characterised the amino acid residues located along the BTG2 and TOB1 interaction surface with Caf1a (CNOT7)/Caf1b (CNOT8) to identify residues required for the interaction. We then analysed the role of BTG2 and TOB1 in the regulation of cell proliferation, translation and mRNA abundance using a mutant that is no longer able to interact with Caf1a (CNOT7)/Caf1b (CNOT8). We conclude that the anti-proliferative activity of BTG/TOB proteins is mediated through interactions with the Caf1a (CNOT7) and Caf1b (CNOT8) deadenylase enzymes. We also demonstrate that recruitment of BTG2 and TOB1 to mRNA leads to reduced protein levels and mRNA degradation. Furthermore, we show that the regulation of mRNA abundance and protein levels is dependent on Caf1a (CNOT7)/Caf1b (CNOT8), but does not appear to require other Ccr4-Not components, including the Ccr4a (CNOT6)/Ccr4b (CNOT6L) deadenylases, or the non-catalytic subunits CNOT1 or CNOT3.